Anal Papilloma: An Exceptional Presentation of Fibrocystic Disease in Anogenital Mammary-Like Glands - Priya Subashchandrabose; Muthuvel Esakkai; Palani Venugopal; Ilavarasan Kannaiyan; Chitra Srinivasan; Punuru Tejashwini Reddy; Evelyn Elizabeth Ebenezer (Case Reports in Pathology)
Previously ectopic breast tissue was thought to be derived from the caudal remnants of the primitive embryonic milk ridges; anogenital mammary-like glands are presently considered as normal constituents of the anogenital region. We report a case of young female, who presented with an anal papilloma. Histopathological examination revealed extensive fibrocystic changes in anogenital mammary-like glands. To date, a lot of benign changes and a wide range of benign and malignant neoplasms have been reported in these glands. However, extensive fibrocystic change of these glands in anal region is very rare. In addition, fibrocystic disease of anal mammary glands, masquerading clinically as an anal papilloma, has not been reported in literature. Hence, it is essential for clinicians and the pathologists to be aware of such a rare presentation. The features of fibrocystic disease in perianal region are also discussed.